Studying nonlinear effects on the early stage of phase ordering using a decomposition method - Copetti, MIM; Krein, G.; Machado, J. M.; de Carvalho, RSM (Elsevier B.V., 2005)
Nonlinear effects on the early stage of phase ordering are studied using Adomian's decomposition method for the Ginzburg-Landau equation for a nonconserved order parameter. While the long-time regime and the linear behavior at short times of the theory are well understood, the onset of nonlinearities at short times and the breaking of the linear theory at different length scales are less understood. In the Adomians decomposition method, the solution is systematically calculated in the form of a polynomial expansion for the order parameter, with a time dependence given as a series expansion. The method is very accurate for short times, which allows to incorporate the short-time dynamics of the nonlinear terms in a analytical and controllable way. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phase ordering; Ginzburg-Landau equation; short-time dynamics; adomians decomposition method